(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Buildings in Indonesia, which has a humid tropical climate, receive direct exposure to sunlight on the roof. The influence of this heat will directly affect the space under the roof and will increase the temperature significantly. Heat transfer is often not taken into account carefully in building physics calculations, even though increasing temperature will affect energy consumption. This research was carried out to determine the distribution of heat and how to prevent the entry of solar heat through the HT-Flux software. The aim of this research is to analyze heat transfer patterns and prevention efforts in buildings. The research method used is an experimental method, where roof construction patterns are tested, to obtain the right roof construction in tropical areas. The result of this research is to obtain damping on the roof by testing it with HT-Flux software.